Nosocomial outbreak of measles amongst a highly vaccinated population in an English hospital setting. Issue 2 (June 2019) - Berry, L.; Palmer, T.; Wells, F.; Williams, E.; Sibal, B.; Timms, J.
Summary: In May 2017 a patient attended the emergency department at a hospital in England, with a presumed allergic reaction. He was subsequently diagnosed with measles. There were seven further confirmed cases, five of whom had received two doses of MMR vaccine. This outbreak highlights the importance of not relying on vaccination status to rule out the diagnosis of measles. Epidemiological investigations of this outbreak were particularly challenging due to the highly infectious nature of the measles virus, and prevented full elucidation of either the source of this outbreak or the transmission pathways.